Fairness in Financial Markets: The Case of High Frequency Trading - Angel, James J.; McCabe, Douglas (2013)
Recent concern over “high frequency trading” (HFT) has called into question the fairness of the practice. What does it mean for a financial market to be “fair”? We first examine how high frequency trading is actually used. High frequency traders often implement traditional beneficial strategies such as market making and arbitrage, although computers can also be used for manipulative strategies as well. We then examine different notions of fairness. Procedural fairness can be viewed from the perspective of equal opportunity, in which all market participants are treated alike. The same rules apply to HFT as to other traders. Another approach to fairness is in the equality of outcomes. Many HFT strategies are beneficial to other market participants, so one cannot categorically denounce the practice as unfair. Other strategies, for both high and low frequency trading, are not. It is thus important to distinguish between the technology and the use of the technology to make judgments on fairness.
Keywords: Manipulation; Financial markets; High frequency trading; Justice; Fairness